An Analysis of Translation Equivalence of Preposition: Equivalence of Preposition “On” in Harry Potter and The Goblet of Fire - Herlina Herlina (ELTE Journal (English Languange Teaching and Education), 2016)
Abstract This research discusses about meaning of preposition “ON” and its equivalence from English into Indonesian and whether or not the equivalence is acceptable and appropriate.  This research uses 241 data and the data are taken from two novels of Harry Potter, Harry Potter and The Goblet of Fire (HG) in English version and Harry Potter dan Piala Api (HP) in Indonesian version.  The researcher uses the theory analysis of Seth Lindstromberg to handle the research problem.  In analyzing this research, the researcher divides preposition “ON” into two meanings i.e. as Literal Meaning (LM) and as Metaphorically Extended Meaning (MEM).  Each of them consists of preposition “ON” ont and onc.  Therefore, LM has LM ont and LM onc, and so does MEM.  On means subject touches landmark.  The superscript ‘t’ stand for touch.  While onc has to do with continuation of movement and the superscript ‘c’ stands for continuation.  However, to make equivalence in preposition “ON” for MEM is not similar with LM even though they have similar explanation of ont and onc.  In translating the preposition “ON’, the equivalence of LM ont are: di atas, di, pada, and waktu.  While LM onc has equivalence when the meaning consist of the following meanings, such as onc vs. off vs. away, onc vs out, and onc vs. toward.  In addition, MEM onc means as continuation of movement.  For MEM ont the meaning must be seen from the context, because MEM can be an idiom, a sentence or a single or one word.  Therefore, MEM t has some functions such as burden metaphor, concerning basis metaphor etc, which depends on the subject and the landmark of preposition “ON”. Keywords: Translation, Preposition ON, Literal Meaning (LM), Metaphorically                   Extended Meaning (MEM), Equivalence.